Antioxidant Properties of Freeze Dried Mix Fruits and Vegetables Product ‘Miss Freezy’ Using Lyophilization Method - Wahyu Widowati; Ariesa Pandanwangi; Teddy Marcus Zakaria; Diah Kusumawaty; Teresa Liliana Wargasetia; Shiela Stefani; Hanna Sari Widya Kusuma; Fadhilah Haifa Zahiroh; Ruth Meiraning Tyas; Vini Ayuni; Syifa Indah Suci Ati (Journal of Nutrition and Food Security)
The proper processing of fruits and vegetable-based food products will improve appearance, taste, bioactivities, and preservation. Freeze-dried (FD) or lyophilization of foods extends shelf life and preserves food's nutritional value and bioactivities. The objective of this study is to compare the antioxidant properties, nutritional value, and vitamins of fresh fruit-vegetables and the combined FD product. Methods: A combination of fruits (mango, papaya, star-fruit, guava, banana, bengkuang), and vegetables (cucumber), called “Miss Freezy” were cleaned with an ozonizer and processed using the lyophilization method. The antioxidant activities measured included 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), 2,2-Diphenyl-1-picrylhydrazyl (DPPH), and Hydrogen Peroxide (H2O2) assay.  While the proximate analysis measured was the determination of water content, ash content, fat content, protein and carbohydrate content, and vitamin C. Results: The value of antioxidant activity in fruit-vegetable combination FD products was higher than in fresh fruit. The median inhibition concentration (IC50) of DPPH, ABTS, and H2O2 scavenging activities were guava 48.74 µg/ml, guava 128.39 µg/ml, and banana 155.55 µg/ml, respectively. The results showed that the water content of fresh fruits, and vegetables was greater than FD products and inversely proportional to the level of ash, fat, protein, carbohydrates, and vitamin C lower than FD products. Conclusions: Based on the results of antioxidant activities, proximate analysis and vitamin C of the FD product was higher than fresh fruits and vegetables. The FD fruit-vegetable combination product can be used as an alternative snack product that is practical and healthy.